The rules of life : a personal code for living a better, happier, more successful kind of life - Templar, Richard, 1950-2006 (Pearson Education, 2015)
With a stunning new look in 2015, and with more new Rules than ever, get ready to experience the Rules effect. Begin to get more out of life, shrug off adversity more easily and generally be a happier, calmer, more fulfilled person. You'll feel the benefits, and so will everyone around you. It's your life. How good could it be?